PKM PENGELOLAAN USAHA PEDAGANG KAKI LIMA DI PASAR TABINGKOTA PADANG - Ariusni -; Syamsul Amar B (LPPM Universitas Ekasakti, 2020)
The objective of the implementation of the Community Partnership Program in the streetvendor partner group of the Tabing market in Padang City is to improve financialmanagement knowledge in street vendors' businesses and households, businessmanagement, access to banks and other financial institutions. The approach method offered to solve partner problems is a) relevant training for street vendors related tobusiness management so that their business can progress and develop, b)businessmanagement so that they can run their business professionally and generate increasedincome, c) access to banking as well as other financial institutions so that they can getadditional capital so that the street vendor business grows. The resultsof the service foundthat (1). the importance of providing knowledge related to additional knowledge about theManagement of Street Vendors Business on Management of Micro, Small and MediumEnterprises (UKMN) so that the businesses they manage are successful and develop so asto increase the income of street vendors in Pasar Tabing, Padang City. (2). With thistraining, new participants understand how to manage business and household finances andmake clear financial records so that their financial books are recorded clearly and (3).New participants know how to easily access banking institutions or other financialinstitutions, namely institutions that provide loans to MSMEs.